ADVOCATE ASSISTANCE AGAINST WITNESSES TOWARD THE SUSPECTED IN THE INVESTIGATION PROCESS OF CORRUPTION CRIMINAL ACT - Alamsyah Bahari (Jurnal Pembaharuan Hukum, 2020)
In order to create a good and transparent criminal justice process so that there is no imbalance between witnesses and law enforcement officials, advocate assistance to witnesses in the investigation process in cases of corruption is necessary because not everyone has mental readiness or knowledge regarding the law in the investigation process. This study aims to provide a complete and clear description of the procedure for examining witnesses who are accused in the process of investigating cases of corruption by authorized institutions and a description of the legal basis for anti-corruption institutions in implementing the prohibition on advocacy assistance to witnesses during the process of investigating criminal cases. corruption. The research method used by researchers is the normative juridical research method. The anomaly in the attitude of the investigator appears when the advocate accompanies a witness who is asked to present it by the reported party or the suspect. Before the examination, the investigator informs the witness that the presence of an Advocate in a witness examination is not obligatory. Advocate witness assistance should also be added to be strictly regulated in the regulations, to prevent unnecessary polemics on this matter. It also includes that the witness has the right to receive a copy of the examination report.